2023
DOI: 10.3390/su152316244
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Impacts of School-Escorted Trips on Traffic Congestion and the Countermeasures in Bangkok: An Agent-Based Simulation Approach

Titipakorn Prakayaphun,
Yoshitsugu Hayashi,
Varameth Vichiensan
et al.

Abstract: The often-discussed issue of parental escorting of children to school and its potential disruption of traffic flow has been extensively examined in the literature. Still, the specific effects of traffic congestion remain understudied. To fill this gap, this study addresses the impacts of school trips on traffic congestion. An agent-based model is applied to simulate various scenarios and assess their impact. Our findings indicate that the traffic speed without school trips is higher speed during peak hours by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…To model traffic performance, some researchers have focused on the behavioral aspect, emphasizing the significant burden placed on families as a result of the inadequacy of public transportation services. This burden means that daily commutes must be arranged for both parents and kids, thus exacerbating the growing reliance on private transportation [1,3]. Their findings concluded that suitable schools are often not located near these families' residences, rendering them inaccessible on foot or by bicycle due to the considerable distances that must be travelled.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To model traffic performance, some researchers have focused on the behavioral aspect, emphasizing the significant burden placed on families as a result of the inadequacy of public transportation services. This burden means that daily commutes must be arranged for both parents and kids, thus exacerbating the growing reliance on private transportation [1,3]. Their findings concluded that suitable schools are often not located near these families' residences, rendering them inaccessible on foot or by bicycle due to the considerable distances that must be travelled.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, the streets in Saudi cities frequently grapple with severe congestion during peak hours, which leads to significant delays, undoubtedly negative frustration, and substantial environmental pollution. In contemporary urban societies, school commutes have emerged as a significant contributor to the decline in traffic operational performance and safety indicators on road networks [1].…”
Section: Introductionmentioning
confidence: 99%